Hi,
having trouble with arranging formulae that have a negative sign. i.e.
a - bx = m
- bx = m - a
x = [m - a][/-b]
thats my working of the problem
but the text book answer is: x = [a - m][/b]
what am I doing wrong?
You haven't done anything wrong.
Remember that $\displaystyle p - q = -(q - p)$ and that a negative times/divided by a negative gives a positive.
So from your working you've ended up with
$\displaystyle x = \frac{m - a}{-b}$
$\displaystyle = \frac{-(a - m)}{-b}$
$\displaystyle = \frac{a - m}{b}$.